2020
DOI: 10.1186/s12909-020-02270-7
|View full text |Cite
|
Sign up to set email alerts
|

Reference letters for subspecialty medicine residency positions: are they valuable for decision-making? Results from a Canadian study

Abstract: Background The letter of recommendation is currently an integral part of applicant selection for residency programs. Internal medicine residents will spend much time and expense completing sub-specialty away electives to obtain a letter of recommendation. The purpose of this study was 1) to examine a large sample of reference letters in order to define essential components of a high-quality letter, and 2) to elucidate the relationship between quality of reference letter and the letter writer. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This finding was illustrated in Chopra’s 5-point composite endpoint, which compared LORs based on the inclusion of 5 components deemed necessary for a LOR to be considered high-quality. They have found that 62.1% of subspecialty medicine PDs/APDs’ LORs included at least 4 out of 5 components, while none of the LORs from elective rotation letter-writers included more than 3 components [ 30 ]. It is possible that PDs and APDs incorporate into LORs information that they themselves most value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was illustrated in Chopra’s 5-point composite endpoint, which compared LORs based on the inclusion of 5 components deemed necessary for a LOR to be considered high-quality. They have found that 62.1% of subspecialty medicine PDs/APDs’ LORs included at least 4 out of 5 components, while none of the LORs from elective rotation letter-writers included more than 3 components [ 30 ]. It is possible that PDs and APDs incorporate into LORs information that they themselves most value.…”
Section: Discussionmentioning
confidence: 99%
“…LORs from PDs and APDs are of much higher quality compared to LORs from non-PDs/APDs and letter-writers from elective rotations. PDs/APDs may serve as the most ideal trainers for letter-writers and future letter evaluators[ 30 ].…”
Section: Discussionmentioning
confidence: 99%